Concept and Application of Digital Twins for Oil-Immersed Power Transformers - Radoman, Uros; Kilibarda, Filip; Kartalovic, Nenad; Miladinović, Nikola; Poluzanski, Vladimir; Vasovic, Valentina; Pejovic, Branko; Zigic, Aleksandar; Lukic, Jelena (Proceedings, Electrical engineering institute "Nikola Tesla", 2024)
This paper provides a literature review and establishes the state-of-the-art in the concept and application of Digital Twin (DT) technology to power transformers. The introductory sections focus on the evolving definition and universal concepts of DT, independent of specific fields of application, as well as the goals of Industry 4.0 and the technologies that enable digital transformation in industry. Special attention is given to the particularities of the power industry, with an emphasis on the unique requirements posed by the nature and importance of oil-filled power transformers, which serve as the foundation for the development of systems based on DT technologies.
Keywords: digital twin; oil-immersed power transformer; literature review; industry 4.0; digital transformation